Identification of Key Circulating Exosomal microRNAs in Gastric Cancer - Qian, Xiaoqing; Xie, Feng; Wei, Huabing; Cui, Daxiang (Frontiers in Oncology, 2021)
Exosomal miRNAs (EmiRs) can be used for prediction of gastric cancer (GC) development. Supposedly, both plasma and urinary microRNA can also be potential biomarkers for screening, but the diagnostic values of EmiRs in blood and urine are not fully studied. We here collected both types of samples from GC patients and healthy individuals and conducted miRNA sequencing to identify key members of EmiRs in GC. The exosomes samples derived from blood and urine were collected from 3 healthy individuals and 7 GC patients. Differentially expressed miRNAs (DE-miRs) were acquired, ontology enrichment analysis and Protein-protein Interaction (PPI) enrichment analysis were performed. There were 5 DE-miRs in the serum and 9 DE-miRs in the urine. For GC patients, there were two up-regulated DE-miRs (miR-142-3p and miR-454-3p) in the serum exosomes, and one up-regulated DE-miR (miR-126-5p) in the urinary exosomes. Using different databases, we found 1231 common targets of miR-126-5p, 243 common targets of miR-142-3p, and 652 common targets of miR-454-3p. Some mRNA targets were shared by two DE-miRs (including TEAD1, HECW2, HECTD1, UBE2W, CD2AP, and CREB1, etc.). Based on these targets, the enriched GO/KEGG/reactome terms were found and they were known cancer related terms. Some key transcription factor may be involved, such as SP1, MEF2, SOX5, and ZNF596, etc. The PPI network show some key nodes, including AAK1, WASL, EPS15, CCDC6, CREB1, NR3C1, TGFBR1, ATG16L1, and QKI. Together, this study provided an integrative analysis of expression profile of key circulating exosomal microRNAs. Three key exosomal miRNAs (miR-142-3p, miR-454-3p, and miR-126-5p) and the interaction network or enrichments based on their targets (like AAK1, WASL, EPS15, CCDC6, NR3C1, ATG16L1, and QKI) may provide a reference of the molecular mechanisms in the GC development.